Optimization of waste banks through assistance in eco-enzyme production as an environmental sustainability effort in Trangsan Village, Sukoharjo - Andi Rezti Maharani; Umda Garit Artiar; Tyas Enggar Cahyani; Agus Triyono (Universitas Muhammadiyah Magelang, 2025)
Trangsan Village, Gatak District, Sukoharjo Regency, has faced environmental challenges related to waste management, particularly organic waste. The establishment of a Waste Bank has successfully addressed the issue of inorganic waste management. However, there has been a lack of innovation in the management of organic waste in an environmentally friendly manner. To address this issue, a community service team initiated a mentoring program for the production of eco-enzyme through the Waste Bank. This activity involved intensive socialization and mentoring for the community, especially the Waste Bank managers and Karang Taruna youth organization. The results of this program indicate an increase in community understanding and skills in processing organic waste, as well as the potential for developing eco-enzyme products as a sustainable environmental effort in Trangsan Village.